2021
DOI: 10.1002/bab.2252
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CASC2 protect ROS‐induced oxidative stress in myocardial infarction by miR‐18a/SIRT2

Abstract: We aimed to investigate the function and its possible mechanisms of long noncoding RNA (lncRNA) in acute myocardial infarction (AMI) model. Patients with AMI and normal volunteers were selected from our hospital. Sprague-Dawley rats were induced into in vivo model of AMI. H9c2 cells were treated with H 2 O 2 to generate injury model. A significantly lower serum gene expression of lncRNA CASC2 was detected. In rat models of AMI, lncRNA CASC2 gene expressions in heart tissue of mice with AMI were decreased. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A number of lncRNAs, miRNAs, and mRNAs are tested to be differentially expressed in the serum of patients with cardiac diseases, nominating them as circulating disease markers (Li et al 2018;Xue et al 2022;Ying et al 2022). Hard-done work of our peers have reported that the aberrant expression of lncRNAs in hypertrophic heart, such as MIAT, RMRP, and Ahit (Zhou et al 2018;Yu et al 2020;…”
Section: Discussionmentioning
confidence: 99%
“…A number of lncRNAs, miRNAs, and mRNAs are tested to be differentially expressed in the serum of patients with cardiac diseases, nominating them as circulating disease markers (Li et al 2018;Xue et al 2022;Ying et al 2022). Hard-done work of our peers have reported that the aberrant expression of lncRNAs in hypertrophic heart, such as MIAT, RMRP, and Ahit (Zhou et al 2018;Yu et al 2020;…”
Section: Discussionmentioning
confidence: 99%
“…The axial elongation can also be promoted by the hypoxia marker upregulated by retinal ischemia, while inhibited by the release of retinal dopamine. DA dopamine Liu et al 2020;Ying et al 2021).…”
Section: Potential Biological Mechanisms Of Air Pollutants On Myopiamentioning
confidence: 99%
“…10 The adhesion and infiltration of neutrophils are the main pathological changes of myocardium after I/R. 11 During this period, the levels of inflammatory factors in myocardial tissue increased significantly, 12 thus causing myocardial damage. Fructus arctii, the dried ripe fruit of Arctium lappa Willd (Asteraceae), has wide pharmacological activities, such as antimicrobial, antioxidant, anti-inflammatory, antiviral, and antitumor activity.…”
Section: Introductionmentioning
confidence: 99%